Spatial variation impact of landscape patterns and land use on water quality across an urbanized watershed in Bentong, Malaysia - Shehab, Zakariya Nafi'; Jamil, Nor Rohaizah; Aris, Ahmad Zaharin; Shafie, Nur Syuhadah (Elsevier BV, 2021)
Landscape patterns and land cover changes critically impact the hydrological cycling of pollutants and affect receiving water quality significantly. Understanding spatial distribution and allocating water pollution sources are vital elements in implementing effective water resource management practices. This research aimed to quantify and illustrate the effects of land use and landscape configuration on water quality in Bentong River, Malaysia. The study sampled 22 sites during the normal and wet season in 2018. FRAGSTATS was used to analyze the spatial change of landscape metrics. Results showed that water quality was closely associated with landscape configurations and land cover proportions. It also indicated that water’s susceptibility to degradation increased with high interspersion of different land uses. Landscape metrics showed that high proportions of edge and patch density for urban and agricultural lands were associated with water quality deterioration, and that water quality could have been better if forests were unfragmented. Factor analysis implied that the river suffered nutrient and organic pollution. Overall, the results inferred that tropical forest was vital in keeping water clean. Consequently, tropical forest can be considered a good indicator of water quality, and can lessen the effects of human practices on ecosystem services. The excessive need for buffer zones along Bentong river was quite evident, as they can provide services by filtering sediment, nutrients and minimizing rainfall variability. It is conceivable that sustaining water connectivity, avoiding land use compactness, controlling unused land proportion and maintaining a prevalent distribution of unfragmented forest can enhance water quality and reduce pollutants’ release.